Role of Lumboperitoneal shunt in CSF diversion: Outcome in common indications and beyond - Aryal, Sameer (Nepal Journal of Neuroscience, 2022)
Dr. Sameer Aryal1, Dr. Ramchandra Shrestha1, Dr. Alok Deo1, Dr. Gopal Raman Sharma11Dhirghayu Guru Hospital, Chabahil, KathmanduIntroduction: A Lumboperitoneal shunt is a procedure of diverting Cerebrospinal Fluid from the lumbar thecal sac to peritoneum. Common indications are Idiopathic Intracranial Hypertension (IIH), Normal Pressure Hydrocephalus (NPH), recurrent CSF fistulas, growing skull fractures etc. It has been often used as a last resort in patients with communicating hydrocephalus who underwent multiple failed ventriculostomy procedures. We present our study of 14 cases of LP shunting done for common indications, we retrospectively analyzed the clinical data of these cases and present our outcome.Objective: Objective of this study was to evaluate the outcome of Lumboperitoneal Shunt and assess its overall role in cerebrospinal fluid diversion procedures.Materials & Methods: Retrospective Study (June 2015- January 2020)Results: A total of 14 cases (6 males and 8 females) were operated from June 2015 to January 2020.Majority of the cases 64.3% (n= 9) were IIH, 21.4% (n=3) were cases of NPH and 14.3% (n=2) were cases of communicating hydrocephalus. Two cases presented with repeat of symptoms after initial improvement and underwent shunt revision. Blockage of thecal catheter due to kinking was found in both cases. Symptomatic improvement was seen in all cases.Conclusion: These results show that Lumboperitoneal Shunt is an excellent option in cerebrospinal fluid diversion whenever indicated. It carries low risk and has good outcome. Key Words: Lumboperitoneal, shunt, theco-peritoneal, idiopathic, benign, intracranial, hypertension, cerebrospinal, fluid, diversion, normal, pressure, hydrocephalus